A guide to agile communication - Defra digital - and DEFRA Digital (Departmetn for Environment, Food & Rural Affairs (UK), 2018)
This guide is intended for: people planning communications activity on behalf of agile teams people doing the communications activity (especially blogging, presenting, or filmmaking) people who manage the people described above, who want to understand what they're doing and why The government service standard encourages teams to work in the open as much as possible, echoing item 10 in the government design principles, “make things open, it makes them better”. This guide was written to help teams do just that.